Wujud Prinsip Kesantunan Berbahasa dalam Film Pendek Cap Cip Top! Produksi Ravacana Films - Sita Nuraseh; Ratna Dwi Dhammayanti (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
Politeness in language is one of the things that must be considered when communicating. It is hoped that this research can provide information or serve as a reference for gaining an understanding of the principles of politeness in the field of pragmatics. This research aims to determine the form of politeness principles according to Leech's theory in the short film Cap-Cip Top!. In this research, the method used is a qualitative descriptive method. The data source used in this research is the short film Cap-cip top! a production by Ravacana Films in collaboration with sambal ABC Indonesia with a duration of 21 minutes and using Javanese in the conversation. The data used in this research are the forms of speech from the characters or players in the film Cap-cip top! which contains the principles of politeness. The data collection technique in this research uses documentation methods and note-taking techniques. Data analysis techniques are carried out in four ways, namely (1) data reduction, (2) data presentation, (3) verification and (4) conclusions. The results of this research found that there were 18 utterances that showed the principles of politeness in the film Cap-cip Top! which consists of 6 utterances of the maxim of acceptance, 9 utterances of the maxim of compatibility/agreement, 1 utterance of the maxim of humility, 2 maxims of generosity and there are no utterances that show the maxim of sympathy or the maxim of wisdom in the film Cap-cip top!. Keywords: Politeness Principles; Cap Cip Top Movies; Pragmatics; Speech Act